A Late Complication of Postpartum HELLP Syndrome: Subarachnoid Hemorrhage Developed at the Postpartum Fourth Day - Ömer Demirtaş; Gülşah Demirtaş; İrfan Tursun; Taylan Şahin; Cevdet Şahin (Gynecology Obstetrics & Reproductive Medicine)
HELLP syndrome is a rare complication of pregnancy which is characterized by hemolysis, elevated liver enzymes, and a low platelet count. The risk of mortality during pregnancy increases with life-threatening complications, and intracranial hemorrhage is the most significant cause of death in pregnant women who have preeclampsia. We represent a case of a 27 year old woman, with 25 weeks of pregnancy diagnosed with subarachnoid hemorrhage developed at the postpartum fouth day. Careful observation and especially rapid and careful management of hypertension can save patients with severe intracranial complications of HELLP syndrome.